Synthesis of 2-Methyl-4-aryl-4,6,7,8-tetrahydro-5(1H)-quinolone Derivatives and their Effects on Potassium Channels - Öztürk, Gökçe Sevim; Vural, Mert; Gündüz, Miyase Gözde; Şimşek, Rahime; Sanoğlu, Yusuf; Şafak, Cihat (Arzneimittelforschung, 2008)
In this study, twelve compounds having 2-methyl-4-aryl-4,6,7,8-tetrahydro-5(1H)-quinolone structure have been synthesized by the reaction of 4-aryl-3-butene-2-on derivatives with 1,3-cyclohexanedione analogs in the presence of ammonium acetate in methanol. The structures of the compounds have been elucidated by IR, 1H-NMR, 13C-NMR, mass spectroscopy and elementel analysis. Their potassium channel opener activities have been investigated on isolated rabbit bladder smooth muscle using pinacidil (CAS 85371-64-8) as standard. The test compounds and pinacidil caused concentration-dependent relaxation responses in bladder smooth muscle strips precontracted with 80 mmol/L KCl with the efficacy order: pinacidil ≥ 3g ≥ 3j ≥ 3a ≥ 3l ≥ 3i ≥ 3c=3b ≥ 3d ≥ 3h ≥ 3k. In bladder smooth muscle strips precontracted with 15 mmol/L KCl, the efficacy order was: pinacidil > 3h ≥ 3c≥ 3j ≥3g ≥3l ≥ 3i=3b ≥ 3k ≥ 3f ≥ 3a. The test compounds and pinacidil caused concentration-dependent inhibition of electrical field stimulation-evoked contractile responses in the bladder smooth muscle strips with the efficacy order: 3j ≥ 3l ≥ pinacidil ≥ 3k ≥ 3h ≥ 3a ≥ 3g ≥ 3c ≥ 3i ≥ 3b ≥ 3f.
Keywords: Potassium channel openers; Quinolones, effects on potassium channels, synthesis